Determinants of Financial Inclusion for MSMEs: Evidence from Indonesia - Gustriani .; Imam Asngari; Suhel .; Ana Yulianita (Universitas Hayam Wuruk Perbanas, 2023)
Enhancing the financial sector is paramount, as it can bolster public trust in financial institutions and consequently expand financial inclusion, particularly within the MSMEs sectors. This study employs the ARCH Maximum Likelihood Model to examine the impact of the banking industry’s financial soundness and macroeconomic conditions on the financial inclusion of MSMEs. The financial soundness of banks is gauged through pertinent financial metrics, including capital adequacy, profitability, credit risk, and liquidity. Moreover, the financial inclusion metric employs the count of account credits per 1,000 adults. The findings reveal that capital, credit risk, and liquidity exert a significant influence on financial inclusion, while profitability and inflation exhibit no significant impact. Furthermore, capital, credit risk, liquidity, and inflation affect MSMEs’ credit, with profitability showing no significant impact. The practical implications derived from these findings underscore the critical importance of upholding the soundness of the banking sector to foster greater financial inclusion in Indonesia. Indonesia should strategically target its efforts toward enhancing the availability of diverse financial products and services tailored to the needs of its MSMEs. By expanding the array of financial products and services for MSMEs, banks stand to access reliable sources of funds for their lending activities.